Analysis of Stock Price Determinants in the Food and Beverage Subsector Companies Listed on the Indonesia Stock Exchange - Ghina Kemala Dewi; Marista Winanti Sutadipraja; M. Naufal Shidqii Dhiyaulhaq; Efa Wahyuni (Jurnal Aplikasi Perpajakan, 2025)
This study aims to analyze the partial and simultaneous influence of Return on Assets (ROA), Return on Equity (ROE), and Earnings Per Share (EPS) on stock prices for food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2022–2023 period. This research uses a quantitative method with purposive sampling technique, resulting in 16 companies being selected as the sample from a total population of 95 companies. Samples were obtained by determining the specified criteria. The type and source of data used is secondary data in the form of financial statements collected thru literature studies and documentation. The data analysis techniques consist of descriptive statistical analysis, classical assumption tests, and multiple linear regression analysis using SPSS Statistics version 27. The results of this study prove that partially, ROA does not affect stock prices with a coefficient of -534.070 and a significance value of 0.826 > 0.05. Meanwhile, ROE and EPS have a positive and significant impact. ROE has a coefficient value of 2325.513 and a significance value of 0.007 < 0.05. EPS has a coefficient value of 2.966 and a significance value of 0.001 < 0.05. Simultaneously, ROA, ROE, and EPS affect stock prices with a significance value of 0.001 < 0.05.